Bench-to-bedside review: Delirium in ICU patients - importance of sleep deprivation - Weinhouse, Gerald L (BioMed Central, 2009)
Delirium occurs frequently in critically ill patients and has been associated with both short-term and long-term consequences. Efforts to decrease delirium prevalence have been directed at identifying and modifying its risk factors. One potentially modifiable risk factor is sleep deprivation. Critically ill patients are known to experience poor sleep quality with severe sleep fragmentation and disruption of sleep architecture. Poor sleep while in the intensive care unit is one of the most common complaints of patients who survive critical illness. The relationship between delirium and sleep deprivation remains controversial. However, studies have demonstrated many similarities between the clinical and physiologic profiles of patients with delirium and sleep deprivation. This article aims to review the literature, the clinical and neurobiologic consequences of sleep deprivation, and the potential relationship between sleep deprivation and delirium in intensive care unit patients. Sleep deprivation may prove to be a modifiable risk factor for the development of delirium with important implications for the acute and long-term outcome of critically ill patients.